Social business efficiency: Instruments development and validation procedure using structural equation modelling - Zainudin, Awang; Habsah, Muda; Fauzilah, Salleh; Abu Shams Mohammad, Mahmudul Hoque; Kamaruzaman, Jusoff (Medwell Journals, 2017)
The efficiency assessment, implementation of appropriate control and responsive measures for Social Business (SB), the concerned bodies need an efficient and inclusive measuring instruments for Social Business Efficiency (SB Efficiency). By pursuing social benefit aims, the profit-making firms under the broad definition of Social Business (SB) can boost the value of their products or services or can exploit new business areas. However, profit-seeking and social benefit aims converging firms reveal a form of SB that has engrossed little deliberation in either theoretical or empirical research on SB Efficiency. Hence, to fill up the research gap, the objectives of this study were two-folds, namely to: measure SB Efficiency in its broadest sense using Structural Equation Modelling (SEM) procedure and determine relevant components for SB Efficiency and develop instruments to measure SB Efficiency in the SME sector. The study found valid and reliable instruments for measuring SB Efficiency. The instruments consist of five components namely Social Value, Social Welfare, Satisfaction, Innovativeness and Resource Leveraging. All components fulfilled the socio-metric properties required of measurement instrument in the social science, namely dimensionality, validity and reliability.